On the Italian public accounts' sustainability: A wavelet approach. (17th August 2020) - Magazzino, Cosimo; Forte, Francesco; Giolli, Lorenzo
Abstract: In this paper we analyse the relationship between public primary deficit and debt for Italian sustainability over the 1862–2013 years. Our empirical strategy uses the wavelet analysis. The evidence confirms the absence of fiscal sustainability in the long‐run for Italy, reinforcing the need for a rebalancing of the public accounts.